Quality assurance in the social care sector : the role of training - (:unkn) unknown (Publications Office of the European Union, 2010)
"The social care sector has expanded into one of the largest providers of jobs. In the EU-27, over 21 million people are employed in the health and social services. This represents a rise of 24 % since 2000 and 10 % of the total workforce in 2009. Yet the field continues to be understaffed and undervalued. Women constitute the vast majority of care workers. Many workers are migrants, who are likely to be less proficient in the local language and new technologies, and possibly less qualified. Moving care away from institutions and into the community also accentuates the need for a more comprehensive skills set. To explore this complex field, Cedefop decided to analyse the generic competences of two groups: front-line workers and managers in community-based services. The study includes a literature review of generic competences, including leadership. In addition, it reports from focus groups set up in five Member States with different social traditions - Germany, Poland, Portugal, Sweden and the UK. These served to identify similarities and differences in social care and to reach a definition of the generic competences needed to respond to the challenges facing Europe. Eighteen case studies of innovative training are examined to determine whether their successes can be duplicated elsewhere. The study ends with policy recommendations, including on quality assurance measures for training." (Hrsg., BIBB-Doku)
Keywords: G 1.2.2.2 Soziale Sicherungssysteme; S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; G 1.2 Arbeitsmarkt; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 2.2 Europa; Sozialpolitik; Pflegeberuf; Sozialberuf; Soziale Dienste; Sozialarbeit; Arbeitsmarkt; Qualifikationsanforderung; Berufsanforderung; Fachwissen; Qualitätssicherung; Fallstudie; Europa